Long non-coding RNA H19, a novel therapeutic target for pancreatic cancer - Jing Wang; Lei Zhao; Kun Shang; Fang Liu; Juanjuan Che; Huihui Li; Bangwei Cao (BMC, 2020)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with high mortality, which threats peoples' health. Unfortunately, the pathogenesis of PDAC remains unclear. Recent studies have indicated that long non-coding RNAs (lncRNAs) can regulate the development and progression of malignant tumors through varying mechanisms. LncRNA H19 has a unique expression profile and can act as a sponger of specific miRNAs to regulate the pathogenic process of many diseases, including PDAC and several other types of cancers. Here, we review the research approaches to understanding the regulatory role of H19 and potential mechanisms in the progression of PDAC and other types of cancers and diseases. These studies suggest that H19 may be a novel therapeutic target for PDAC and our findings may open new revenues for scientific researches and development of valuable therapies for these diseases in the future.